From Where Does Innovation Come? Employee Well-Being and Organizational Commitment Induced by Leadership Style - Lu-Jui Chen; Han Lee; Wen-Ruey Lee; Siou-Hua Yi (Journal of Management Research, 2024)
Companies require good management practices to enhance their competitive advantage. The goal of this study is to examine the impact of leadership style, specifically how it induces employee well-being and organizational commitment. This study suggests that the management style of leaders is a key prerequisite for creating a good work environment and inducing innovation in employees. Therefore, this study uses the concepts of leadership style, employee well-being, organizational commitment, and innovation to analyze a sample of 349 respondents in the workplace. Theoretical and hypothetical investigation through causality testing using statistical tools of path analysis. The results indicate that transformational leadership and transactional leadership increase employee well-being and innovation. When employees feel satisfied, they increase their commitment to the organization, which in turn increases their innovation. In conclusion, companies need to be able to emphasize integration in their leadership styles. How to switch or match leadership styles is an important issue for leaders.